Inclusion as a Moral Challenge: the Potential of the Konstanz Method of Dilemma Discussion® (KMDD®) - Reinicke, Martina (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
This article presents the Konstanz Method of Dilemma Discussion ® (KMDD ®) and explains the integration of the KMDD ® in ethics lessons. In this paper, some special learning effects of this inclusive teaching and learning method are shown. Furthermore, it investigates the questions of how to achieve more knowledge in ethics lessons by dialogue and how to realize better moral development, particularly by handling of differentiation. Moral education of all participants who are involved in the learning process (learners and teacher alike) is a crucial task of every true inclusion. True inclusion means building optimal learning conditions in keeping with the free will of all participants. Because our society is transforming constantly in both global and demographic aspects, coping with these challenges is mandatory.